STRATEGI PROGRAM AFTERNOON DELIGHT DALAM MEMPERTAHANKAN EKSISTENSI DI RADIO KISI 93.4 FM BOGOR - Atala, Dimas KR; Rusfien, Ismail Taufik (Media Bahasa, Sastra, dan Budaya Wahana, 2024)
Every radio station can make a broadcast program, but after making a broadcast program rado station must make the program continue to survive and remain in demand and liked by its listeners. So that the program can maintain its existence. Therefore, to stay on the air and survive in the broadcasting industry. KISI 93.4 FM carries out a program strategy to survive. This research was conducted with the aim of finding out the strategy of the Afternoon Delight program in maintaining its existence on KISI 93.4 FM radio Bogor The method in this study uses a qualitative method and for data collection techniques using observation, interviews, and document collection related to this research. The results of this study show that the Afternoon Delight program in maintaining its existence on KISI 93.4 FM radio, by planning the program, namely by implementing short-term meetings for short KISI FM wants to make a Ramadan program, and help UMKM entrepreneurs. and want to conduct a trial for the program to be created. For the middle class, KISI FM wants to make a plan for the grid goes to school. And for the long term, KISI FM wants many brands or advertisements to enter its programs. In the production of the KISI FM program, it considers the originality of the program it makes. For the execution of the program, KISI FM tries to understand the habits of listeners by presenting the latest and relevant information. For program monitoring and evaluation, KISI FM conducts program evaluations obtained through various channels, such as social media, Instagram and WhatsApp, telephone, email, or comments directly from listeners.